Pilocytic Astrocytoma with Gangliocytic Differentiation to Pilomyxoid Astrocytoma-expanding the Morphological Spectrum: Case Report and Literature Review - Gupta, Kirti (Asian J Neurosurg, 2018)
We present a rare case of pilocytic astrocytoma (PA) with gangliocytic differentiation arising in the suprasellar/chiasmatic region in a young boy that showed a rapid regrowth after the 1(st) subtotal resection and “differentiated” into pilomyxoid astrocytoma (PMA) in subsequent recurrences. The clinical course, imaging, and histological features have been described with a review of the literature. While PA is well-circumscribed, biphasic tumors with bipolar piloid cells, those arising in the diencephalic region often contain myxoid stroma, angiocentric pattern, and “intermediate” features between PA and PMA. Examples of PMA “maturing” to PA are also on record; however, PA with gangliocytic component differentiating to PMA has not been described in the literature to the best of our knowledge.